2008
DOI: 10.1103/physrevlett.100.097001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a 500 meV Collective Mode inLa2xSrxCuO4andNd2

Abstract: Utilizing resonant inelastic x-ray scattering, we report a previously unobserved mode in the excitation spectrum of La2-xSrxCuO4 and Nd2CuO4 at 500 meV. The mode is peaked around the (pi, 0) point in reciprocal space and is observed to soften, and broaden, away from this point. Samples with x=0, 0.01, 0.05, and 0.17 were studied. The new mode is found to be rapidly suppressed with increasing Sr content and is absent at x=0.17, where it is replaced by a continuum of excitations. This mode is only observed when … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
124
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(135 citation statements)
references
References 34 publications
10
124
1
Order By: Relevance
“…[4][5][6][7] Hill et al have succeeded in detecting the magnetic excitation spectra peaked around 500 meV energy region at the Cu K-edge in La 2 CuO 4 . 4 The following theories have revealed that the obtained signals are attributed to the two-magnon excitation from the antiferromagnetic (AFM) ground state brought about by the presence of the core hole potential during the intermediate states. [8][9][10] Since then, plenty of measurements have been reported out at the Cu K-edge as well as Cu L 3 -edge.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Hill et al have succeeded in detecting the magnetic excitation spectra peaked around 500 meV energy region at the Cu K-edge in La 2 CuO 4 . 4 The following theories have revealed that the obtained signals are attributed to the two-magnon excitation from the antiferromagnetic (AFM) ground state brought about by the presence of the core hole potential during the intermediate states. [8][9][10] Since then, plenty of measurements have been reported out at the Cu K-edge as well as Cu L 3 -edge.…”
Section: Introductionmentioning
confidence: 99%
“…Resonant X-ray emission spectroscopy (de Groot & Kotani, 2008) and X-rayRaman-scattering-based XANES (Gordon et al, 2008) would profit from an energy resolution of ÁE ' 300 meV. Resonant IXS, for example at the K, L and M edges of 3d, 4d and 5d transition metals, with ÁE < $ 100 meV is nowadays a powerful tool for studying collective magnetic and orbital excitations (Hill et al, 2005;Schlappa et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An independent picture of magnetic and charge excitations has now been gained by resonant inelastic X-ray scattering (RIXS) experiments at the Cu K edge 22 and Cu L 3 edge [23][24][25][26][27][28] in the cuprates and at the Fe L 3 edge in the iron pnictides 29 . RIXS offers some interesting advantages, such as the possibility of measuring small-volume samples, additional flexibility from polarization control and complementary information from the Cu (single magnons) and O (two magnons) edges 30 .…”
mentioning
confidence: 99%